Biography of Muhammad TWH (Tok Wan Haria), a Journalism Figure from North Sumatra - Sri Ramadina Tanjung; Laila Rohani; Kasron Muhsin Nasution (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the biography of Muhammad TWH (Tok Wan Haria), a journalistic figure from North Sumatra, by tracing his background, education, and career in the press. The research employed historical methods, encompassing heuristics, source verification, interpretation, and historiography, grounded in historical and biographical theory. The results indicate that Muhammad TWH was born in Geudong, North Aceh, on November 15, 1932, and was a freedom fighter and journalist who played a significant role in the development of the press in North Sumatra. His career progressed through various organizations, such as SIWO PWI, PSMS Medan, and veterans' organizations. He also served as a member of the Regional People's Representative Council (DPRD). In addition to his active work as a journalist covering various national and international events, Muhammad TWH also contributed significantly to the preservation of press history by establishing the North Sumatra Press Struggle Museum and receiving an award as a veteran during the Soeharto administration.